“Elas podem”: a banda endometriose e a participação feminina no cenário roqueiro em Feira de Santana – Ba (2006-2011) - Almeida, Patrícia Matos (2019)
Thisworkaimedtoreflectonfemaleparticipation in rock throughtheexperiencesof Endometriose, a feminist punk rock / hardcore bandthatexistedbetweentheyearsof 2006 and 2011 in thecityof Feira de Santana, Bahia. The groupwasformedbyyoung girls whowere 14 and 19 yearsold. In thisway, ourresearchwasbasedongenderstudies in a clearintersectionwiththenotionofyouth. The researchalsohadontherelationshipbetweenfeminismand rock, especiallythroughthe look atthe American youthcultureofriot grrrl, in additiontohavingcreated a participation in this musical genrebeyondthe Feirenseband. Thisisbecause, throughaspectsthatinvolvethetrajectoriesof some stories that stand out in theinternationalandnationalmarket, theyreflectthemontheasymmetriesofpowerstimulatedbytheconflictsofgenre in the rock. Futher, wediscussedtheprocessofformingthe musical andfeministidentityof Endometrioseandthedialogues it establishedwiththe local rock scene